Sex differences and the role of sex hormones in face development and face processing - Mareckova, Klara (2013)
Sex differences have been identified in both external appearance of faces (e.g. Bulygina et al., 2006; Weston et al., 2007) and the way information about faces is extracted by our brains, that is in face processing (e.g. Tahmasebi et al., 2012; Hampson et al., 2006). The mechanisms leading to the development of such sex differences are not well understood. This thesis explores the role of sex hormones in face development and face processing. Data from two large-scale studies (Saguenay Youth Study and Imagen, with n=1,000 and 2,000, respectively) and four smaller datasets (Cycle-Pill Study, n=20; Pill Study, n=20; First Impression Study, n=120, and Twin Study, n=119) were used to explore the effects of sex and sex hormones on face development (head MR images, MRI-face reconstruction) and face processing (functional MRI data, eye-tracking data). Shape of male and female faces was influenced by both prenatal and pubertal androgens. Facial signature of prenatal androgens, identified by the sex-discordant twin design, was found also in an independent dataset of female adolescents (singletons) and we showed that prenatal androgens, indexed indirectly by the facial signature, were associated with larger brain size. We propose that this facial signature might be used, similarly to digit ratio, as an indirect index of prenatal androgens. Variability in postnatal sex hormones due to the use of oral contraception and the phase of menstrual cycle influenced brain response to faces. Using the same dynamic face stimuli as in the functional magnetic resonance imaging (fMRI) study, we showed that eye-movements scanning the face did not differ between the users and non-users of oral contraception. We conclude that effects of sex hormones can be observed in both the face and the brain and that these effects help us understand sex differences in face shape and face processing.